Cape Verde : Fourth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Request for Waiver of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2004)
This paper discusses Cape Verde's Fourth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility (PRGF) and Request for Waiver of Performance Criteria. Economic performance in 2003 was better than programmed in many respects: real GDP growth was higher, inflation was lower, the fiscal and external current account deficits were smaller, and the terms of trade were stronger. Stronger economic growth reflected the continued rapid growth in tourism and a rebound in agriculture following drought conditions in 2002.